Effects of ship-breaking activities on the abundance and diversity of macrobenthos in Sitakundu Coast, Bangladesh - Mohammad Belal Hossain; MD. ABU NOMAN; JAHANARA AKHTER LIPI; ABU HENA MUSTAFA KAMAL; MOHD HANAFI IDRIS (Society for Indonesian Biodiversity, 2020)
Abstract. Lipi JA, Noman MDA, Hossain MB, Abu Hena MK, Idris MH. 2020. Effects of ship-breaking activities on the abundance and diversity of macrobenthos in Sitakundu Coast, Bangladesh. Biodiversitas 21: 5085-5093. To articulate the ecological processes or anthropogenic impacts, it is necessary to explore various distributional patterns of benthic communities. The study was conducted to investigate the variability of macrobenthos between a ship braking and non-ship-breaking area along the Sitakunda coast, Chittagong, Bangladesh. This is the first comprehensive study that addresses the effects of ship-breaking activities on the variability of benthic communities in the study area. Macrobenthos were sampled from two different regions namely Bhatiary (ship-breaking area) and Banshbaria (non-ship-breaking area/reference area) in two different time periods (April and July) for comparative analyses. During the study period, Polychaeta was the most dominant group comprising 60% of the total macrobenthos all over the study area. Macrobenthos abundance and diversity demonstrated strong spatial variability. The mean abundance varied from 3799.75±3452.28 ind./m2 to 4107.25±2743.6 ind./m2 from the ship-breaking to non-ship-breaking area. Similar to macrobenthos abundance, the diversity index (H?) (varied between 2.45 and 1.85), species richness (D) (varied between 1.99 and 1.04), and the number of taxa (varied between 17.25 and 9.25) were higher in the non-ship-breaking area compared to the ship-breaking area. Multivariate analyses, nMDS, and CCA plot showed a distinct grouping for different location. Besides, the diversity indices of the Polychaeta community, and the presence or absence of several pollution indicator taxa revealed that Bhatiary (the ship-breaking area) was confronting deleterious effects of ship-breaking activities.